COVID-19 and the Challenges to the Healthcare System in Iran - Mousa Bamir; Reza Sadeghi (Kerman University of Medical Sciences, 2023)
The sudden spread of the coronavirus in the world has affected the healthcare system of countries worldwide, while the policymakers did not have enough time to adapt and adjust the response, which has led to unprecedented disruption in the global healthcare system. Since the healthcare system of any country is the basic foundation for to fight against COVID-19 at the national level, the question has become a serious concern, is the current healthcare system qualified to respond to the pandemic?. Evidence shows that, despite all advances in the past decades, the sudden outbreak of Covid-19 has made health care systems incapable of managing the disease, especially in the field of diagnosis and screening. In Iran, besides all the common challenges of COVID-19, international sanctions and the traditional nature of the healthcare system have doubled the challenge of controlling Covid-19. Iran's healthcare system must be updated based on artificial intelligence technology and the Internet of Things to deal with the present and possible future mutations. Remote medicine and care are among the most critical components. This update leads to reducing face-to-face visits, remote service delivery, clinical decision-making, compensating for the lack of human resources, and creating patient-centered collaboration through the medical data sharing system to prevent the spread of the virus. And finally, it is essential to use the experiences of other countries to improve the health system. Establishing public-private partnership Entering, empowering, training, and enhancing the skills of the medical community to adapt to digital methods and technologies, implementing the public health care system, paying attention to the technology of hardware and software infrastructures and the culture of using Information technology in the health system helps in improving the structure from being traditional to digital.